Concomitant antihypertensive medication and outcome of patients with metastatic castration‐resistant prostate cancer receiving enzalutamide or abiraterone acetate - Ondřej Fiala; Petr Hošek; Hana Korunková; Milan Hora; Jiří Kolář; Ondřej Šorejs; Ondřej Topolčan; Jan Filipovský; Václav Liška; Matteo Santoni; Sebastiano Buti; Jindřich Fínek (Cancer Medicine, 2024)
Abstract Background The introduction of novel hormonal therapies represented by enzalutamide (ENZ) and abiraterone acetate (ABI) has reached a great progress in the treatment of metastatic castration‐resistant prostate cancer (mCRPC). The majority of mCRPC patients are elderly suffering from chronic co‐morbidities requiring use of various concomitant medications. In the present study, we focused on impact of concomitant antihypertensive medication on the outcomes of mCRPC patients treated with ENZ or ABI. Methods In total, 300 patients were included and their clinical data were retrospectively analyzed. Results Angiotensin‐converting enzyme inhibitors (ACEIs) represented the only concomitant medication significantly associated with survival. The median radiographic progression‐free survival (rPFS) and overall survival (OS) for patients using ACEIs were 15.5 and 32.3 months compared to 10.7 and 24.0 months for those not using ACEIs (p = 0.0053 and p = 0.0238, respectively). Cox multivariable analysis revealed the use of ACEIs a significant predictive factor for both rPFS (HR = 0.704, p = 0.0364) and OS (HR = 0.592, p = 0.0185). Conclusion The findings of this study suggest an association between the concomitant use of ACEIs and longer survival of mCRPC patients receiving ENZ or ABI therapy.